2008
DOI: 10.1021/ac800269x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Model of Resonant Polymer-Coated Microcantilevers in Viscous Liquid Media

Abstract: Expressions describing the resonant frequency and quality factor of a dynamically driven, polymer-coated microcantilever in a viscous liquid medium have been obtained. These generalized formulas are used to describe the effects the operational medium and the viscoelastic coating have on the device sensitivity when used in liquid-phase chemical sensing applications. Shifts in the resonant frequency are normally assumed proportional to the mass of sorbed analyte in the sensing layer. However, the expression for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
(61 reference statements)
0
26
0
Order By: Relevance
“…These studies were motivated by the goal of reducing the detrimental effects of fluid damping and fluid inertia, thus providing higher resonant frequencies, fres, and quality factors, Q, the latter corresponding to sharper resonance peaks. Such improvements in the resonant characteristics of the device translate into corresponding enhancements in sensor sensitivity and limit of detection, especially for liquid-phase detection [6,10]. Some of the previously mentioned studies on the use of the inplane flexural mode demonstrated both theoretically [3,4,8] and experimentally [5,7] that the improvements in the in-liquid resonant characteristics will be most pronounced in microcantilevers that are relatively short and wide.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were motivated by the goal of reducing the detrimental effects of fluid damping and fluid inertia, thus providing higher resonant frequencies, fres, and quality factors, Q, the latter corresponding to sharper resonance peaks. Such improvements in the resonant characteristics of the device translate into corresponding enhancements in sensor sensitivity and limit of detection, especially for liquid-phase detection [6,10]. Some of the previously mentioned studies on the use of the inplane flexural mode demonstrated both theoretically [3,4,8] and experimentally [5,7] that the improvements in the in-liquid resonant characteristics will be most pronounced in microcantilevers that are relatively short and wide.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation does not account for changes in resonator stiffness due to the analyte absorption; while this is a reasonable assumption for the case of thin polymeric films on top of silicon resonators as studied herein, stiffness effects may substantially change the characteristics of a mass-sensitive sensor for other conditions. 21 If the analyte concentration cA is given in parts per million (v/v), the analyte sensitivity SA may be calculated as accessed by following the link in the citation at the bottom of the page.…”
mentioning
confidence: 99%
“…The total displacement at the tip is the relevant response quantity for sensor applications that utilize optical (laser) monitoring of the tip position, while the tip's bending-deformation displacement at or near resonance will be approximately proportional to the beam's bending strain, i.e., it will correspond to the output signal of sensors that employ local piezoresistive elements for monitoring beam response (e.g., the piezoresistive Wheatstone bridge employed in [19] [20,[29][30][31]). …”
Section: Problem Statementmentioning
confidence: 99%
“…All of these studies were primarily motivated by the desire to reduce the detrimental effects of fluid damping and fluid inertia, thus providing higher resonant frequencies, fres , and quality factors, Q , the latter corresponding to sharper resonant peaks. Within the context of sensing applications, such improvements in the resonant characteristics correspond to enhancements in sensor performance metrics such as mass or chemical sensitivity and limit of detection, especially for liquid-phase detection (e.g., [20,[29][30][31]). …”
Section: Introductionmentioning
confidence: 99%